Ultra Vires Kewenangan Kemenkumham sebagai Pengadilan Non-Litigasi dalam Sistem Ketatanegaraan Indonesia - Ahmad Gelora Mahardika (Universitas Serang Raya, 2019)
The decision of the Constitutional Court Number 56 / PUU-XIV / 2016 revoked the permit for the Government to request a Regional Regulation and hand over the authority to the Supreme Court. However, the Government through the Ministry of Law and Human Rights then issued Regulation of the Minister of Law and Human Rights No. 32 of 2017 concerning Procedures for Settling Disputes in Legislation through the Non-litigation Path which in principle provided permits to support the Directorate General of Regulation. Initially this authority did not exist in the Minister of Law and Human Rights Regulation of the Republic of Indonesia Number 29 of 2015 concerning Organization and Work Procedure of the Ministry of Law and Human Rights of the Republic of Indonesia, but then the authority was regulated in Republic of Indonesia Minister of Law and Human Rights Regulation Number 24 Year 2018 Regarding the Third Amendment to the Regulation of the Minister of Law and Human Rights Number 29 of 2015 concerning the Organization and Work Procedure of the Ministry of Law and Human Rights of the Republic of Indonesia. Besides inconstitutional, after being approved, it was also stipulated by law, this authority was also previously owned.